Effect of dates of planting and spacing on growth and yield characteristics of ginger (Zingiber officinale Ros.) var. IISR Mahima - R G Khandekar, A R Yadav, R N Nawale, G N Korake, (Journal of Spices and Aromatic Crops, 2013)
A field trial was carried out with an objective to determine the optimum date of rhizome planting and spacing to obtain good growth and yield of ginger var. ‘IISR Mahima’ at Dapoli (Maharashtra). The experiment was laid out in split plot design with planting dates as main plot treatments (15th April, 1st May, 15th May, 30th May and 15th June) and intra row spacing as sub plot treatments (25 cm × 15 cm, 25 cm × 25 cm and 25 cm × 35 cm) in three replications. It is evident from the results that dates of planting had significant effect on almost all the characters under study. Planting of rhizomes on 15th April showed better growth, yield and yield attributing characters. Among spacing levels, the closer spacing of 25 cm × 15 cm recorded significantly higher plant height, green and dry ginger yield. The interaction treatments showed significant effect for most of the characters except for number of days required for sprouting, per cent sprouting and finger characters. Among the various treatment combinations planting on 15th April and 25 cm × 15 cm spacing exhibited higher plant height, yield of green (40.16 t ha-1) and dry ginger (8.58 t ha-1). Planting after 15th May with wider spacing 25 cm × 35 cm resulted in lower yield.